Fluorinated nanocellulose-reinforced all-organic flexible ferroelectric nanocomposites for energy generation - Ram, Farsa; Ambone, Tushar; Sharma, Aakash; Murugesan, Rajarathinam; Kajale, Deepak; Borkar, Vivek; Ali, Shaikh Faruque; Balu, Praveen Kumar; Kumaraswamy, Guruswamy; Shanmuganathan, Kadhiravan (Journal of Physical Chemistry C, 2018)
We report here enhanced ferroelectric crystal formation and energy generation properties of polyvinylidene fluoride (PVDF) in the presence of surface-modified crystalline nanocellulose. Incorporation of only 2-5 wt % fluorinated nanocellulose (FNC) in PVDF has been found to significantly induce polar beta/gamma-phase crystallization as compared to the addition of unmodified nanocellulose (carboxylated nanocellulose). A device made up of electrically poled PVDF/FNC composite films yielded 2 orders of magnitude higher voltage output than neat PVDF in vibrational energy harvesting. This remarkable increase in energy generation properties of PVDF at such a low loading of an organic natural biopolymer could be attributed to the tailored surface chemistry of nanocellulose, facilitating strong interfacial interactions between PVDF and FNC. Interestingly, energy harvesting devices fabricated from PVDF/FNC nanocomposites charged a 4.7 mu F capacitor at significantly faster rate and the accumulated voltage on capacitor was 3.8 times greater than neat PVDF. The fact that PVDF/FNC nanocomposites still retain a strain at break of 10-15% and can charge a capacitor in few seconds suggests potential use of these nanocomposites as flexible energy harvesting materials at large strain conditions.